2018
DOI: 10.18410/jebmh/2018/581
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Neoplastic Lesions of Female Genital Tract in Kolhan, Jharkhand

Abstract: BACKGROUND Gynaecological specimens form the major proportion of tissue biopsies in most pathology departments. Sexually active women are more prone to cervical disease. The aim of this study is to find out the frequency distribution of tumours occurring in FGT. MATERIALS AND METHODS This study was carried out in pathology department of MGM Medical College, Jamshedpur. All formalin fixed surgical specimens of female genital tract from January 2013 to December 2015 were subjected for histopathology and examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
2
2
1
Order By: Relevance
“…Similar observations were also noted in the study by Khandekar S et al (6.28%) [15] while other studies by Gaikwad SL et al [12] , Singh M et al et al [16] and Paul SN et al [13] reported squamous cell carcinoma as 9.28%,7.04% and 7% respectively. In our study, the other histological variant of cervical carcinoma reported was a single case of small cell carcinoma in the age group of 41-50 years.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar observations were also noted in the study by Khandekar S et al (6.28%) [15] while other studies by Gaikwad SL et al [12] , Singh M et al et al [16] and Paul SN et al [13] reported squamous cell carcinoma as 9.28%,7.04% and 7% respectively. In our study, the other histological variant of cervical carcinoma reported was a single case of small cell carcinoma in the age group of 41-50 years.…”
Section: Discussionsupporting
confidence: 89%
“…Among the total neoplastic lesions in the present study, 77.93% were benign lesions. Similarly in a study done by Paul S N et al [13] , 90% lesions were reported as benign lesions among the total neoplastic lesions which is higher compared to our study. In the present study, benign lesions of cervix reported were endocervical polyp (9.65%) followed by squamous metaplasia and cervical leiomyoma with majority of the cases in 31-40 and 41-50 years of age.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations